Tulevaisuuden toimitusketju – vaikutuksia siviili- ja sotilaslogistiikkaan - Sini Laari; Sari Uusipaavalniemi; Risto Leinonen; Lauri Ojala (Suomen Sotatieteellinen Seura ry, 2022)
The present study examines the implications of six trends in supply chain management (SCM) and logistics on civilian and military supply chains over the next two decades. The data was collected from a targeted sample of SCM/ logistics researchers and managers of the largest manufacturing, trading and
logistics firms in Finland in 2016–2017 and from logistics experts in the Finnish Defence Forces (FDF) in 2017. The respondents assessed six SCM trends by 2035: 1) globalisation of supply chains (SC); 2) digitalisation and automation of logistics processes; 3) dependence on electricity and IT systems; 4) hybrid
warfare activities targeted at SCs; 5) resource scarcity/circular economy/sharing economy; and 6) building SC resilience. The results suggest that the export restrictions on military products and concerns on security of supply limit the possibilities of the FDF to fully benefit from the trends. The priorities and motives may also be different. Business SCs tend to be at the forefront of the development of new practices and technologies but mainly under normal circumstances. The FDF will need to ensure operations under emergencies meaning that some of the solutions are not applicable as such in the military context. Building up resilience will be equally important in the increasingly volatile environment. Ensuring the availability of qualified personnel will be a key challenge for both civilian and military organisations.